The Effect of Gross Domestic Product and Inflation on Value-Added Tax Revenue in Indonesia - Tengku Eka Susilawaty; Nancy Mayriski Siregar; Rifqy Cheviandri (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to explore and empirically test the impact of Gross Domestic Product (GDP) and inflation on value-added tax (VAT) receipts. The research was conducted in Indonesia over the period from 1993 to 2022, using a sample of 30 observations on GDP, inflation and VAT. The sampling method employed was non-probability sampling with a saturation sampling technique, where the entire population was used as the sample. The analysis technique applied was multiple linear regression. The results indicate that, individually, GDP has a significant effect on VAT receipts (t-value > t-table) 2.064 > 2.059; an increase in GDP is likely to enhance VAT receipts due to the increase in household income, which supports the consumption of goods and services. In contrast, inflation does not have a significant effect on VAT receipts (t-value < t-table) 1.470 < 2.059; despite rising inflation, VAT receipts remain stable due to government policies on price controls, subsidies, and other measures to stabilize prices. Collectively, GDP and inflation together account for 98.2% of the effect on VAT receipts. Future research is recommended to include additional variables from both internal and external factors, such as government policies or global economic conditions, to gain a deeper understanding of other determinants affecting VAT receipts beyond GDP and inflation.